Factors Affecting Performance of Commercial Banks in Uganda A Case for Domestic Commercial Banks - Nsambu Kijjambu, Frederick (International Business Research Conference, 2014)
The study seeks to establish the underlying factors responsible for performance of domestic commercial banks in Uganda. The factors are analyzed in the light of structure–conduct performance (SCP) and Efficiency hypothesizes (ES). This is supplemented by Global advantage theory together with Home field theory. The study analyses performance of all licensed domestic and foreign commercial banks independently on average basis. Using Linear multiple regression analysis over the period 2000-2011, the study found that, management efficiency; asset quality; interest income; capital adequacy and inflation are factors affecting the performance of domestic commercial banks in Uganda over the period 2000-2011. Policy implications emerged for commercial banks’ management includes; efficient management; credit risk management; capital adequacy levels; diversification and commercial bank investment. In addition, monetary policy regulations and instruments should not enforce high liquidity and capital adequacy levels. Regulations on non-interest income activities should be put in place to harmonize the impact of diversification on all commercial banks’ performance and to avoid exploitation of bank customers.
Keywords: Bank performance; Internal and External factors; Financial ratios; Uganda